2022
DOI: 10.7759/cureus.30723
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia Telangiectasia Presenting as Cervical Dystonia

Abstract: The ataxia telangiectasia mutant (ATM) protein is a sensor and signal transducer that amplifies and communicates signals of DNA damage further to the mediators of cell cycle arrest, apoptosis, and senescence (p16, p19, p21, BAX etc.) which is modified by the strength of the cellular stress. They are able to act as recognition and signaling proteins because of their kinase activity. Classic ataxia telangiectasia is associated with homozygous mutations of the ATM gene, the complete absence of its kinase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…After reviewed previously published literatures of genetically confirmed A-T cases with predominant dystonia, we found that dystonia-dominant A-T cases may have a significantly different clinical picture compared to the typical A-T. In total, 13 pedigrees including 30 patients with ATM mutations were reviewed ( 7 , 10 18 ) ( Table 1 ). The median age of onset was 10.67 years, ranging from 1 to 20 years old.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewed previously published literatures of genetically confirmed A-T cases with predominant dystonia, we found that dystonia-dominant A-T cases may have a significantly different clinical picture compared to the typical A-T. In total, 13 pedigrees including 30 patients with ATM mutations were reviewed ( 7 , 10 18 ) ( Table 1 ). The median age of onset was 10.67 years, ranging from 1 to 20 years old.…”
Section: Discussionmentioning
confidence: 99%
“… Abbreviations: ANO3 —anoctamin 3 [ 31 ]; ATM —ataxia-telangiectasia mutated [ 32 ]; ATP7B —ATPase copper transporting beta [ 33 ]; C19orf12 —chromosome 19 open reading frame 12 [ 34 ]; CACNA1A —calcium channel, voltage-dependent, P/Q type, alpha-1A subunit [ 35 ]; CACNA1B —calcium channel, voltage-dependent, N type, alpha-1B subunit [ 36 ]; CIZ1 —CIP1-interacting zinc finger protein [ 37 ]; COL6A3 —collagen, type VI, alpha-3 [ 38 ]; CP —ceruloplasmin [ 39 ]; DRD5 —dopamine receptor D5 [ 40 ]; FTL —ferritin light chain [ 41 ]; FUS —fused in sarcoma [ 15 ]; GCH1 —GTP cyclohydrolase 1 [ 42 ]; GNAL —guanine nucleotide-binding protein alpha-activating activity polypeptide, olfactory type [ 20 ]; KMT2B —lysine-specific methyltransferase 2B [ 43 ]; LRRK2 —leucine-rich repeat kinase 2 [ 15 ]; PANK2 —pantothenate kinase 2 [ 44 ]; PRKRA —protein kinase, interferon-inducible double-stranded RNA-dependent activator [ 17 ]; RAB12 —RAS-associated protein RAB12 [ 45 ]; REEP4 —receptor expression-enhancing protein 4 [ 16 ]; SGCE —sarcoglycan, epsilon [ 46 ]; SPR —sepiapterin reductase [ 47 ]; SYNE1 —spectrin repeat-containing nuclear envelope protein 1 [ 15 ]; TH —tyrosine hydroxylase [ 48 ]; THAP1 —THAP domain-containing protein 1 [ 49 ]; TOR1A —torsin 1A [ 50 ]; TUBB4A —tubulin, beta-4A [ 51 ]; VPS16 —VPS16 core subunit of corvet and HOPS complexes [ 52 ]; VPS41 —VPS41 subunit of HOPS complex [ 21 ]; WDR45 —WD repeat-containing protein 45 [ 53 ]. …”
Section: Figurementioning
confidence: 99%
“…J Neurol Neurosurg Psychiatry Res 2023; 5 (1): 109. doi: 10.31531/edwiser.jnnpr.1000109 movement disorders such as dystonia, choreoathetosis, myoclonus, and tremors. General physical appearance is characterized by the presence of short stature, café au lait spots, progeric skin and hair changes, oculocutaneous telangiectasia, horizontal head thrusts due to difficulty in initiating horizontal saccades (both voluntary and reflex saccades are affected), ocular apraxia, diabetes mellitus, and features of glucose intolerance like acanthosis nigricans, hypogonadism, lymphocytopenias, predisposition to malignancy, hypoimmunoglobulinemia, and other immune defects [2].…”
Section: Introductionmentioning
confidence: 99%